2019
DOI: 10.1111/1756-185x.13529
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 and interleukin‐17 are related to depression in patients with rheumatoid arthritis

Abstract: Aim: Mood disorders are a serious issue for patients with rheumatoid arthritis (RA) because poor mental health can exacerbate the disease course. This study aimed to identify the effect of proinflammatory cytokines on the mood of patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 26 publications
3
38
1
2
Order By: Relevance
“…No significant differences were found between the values of depression ratings and the IL-6 levels. However, a study in Taiwan with 113 RA patients and 42 healthy controls demonstrated elevated serum IL-6 and IL-17 levels in RA patients with depressive symptoms [74].…”
Section: Il-6 In Physical Diseases Associated With Depressionmentioning
confidence: 96%
“…No significant differences were found between the values of depression ratings and the IL-6 levels. However, a study in Taiwan with 113 RA patients and 42 healthy controls demonstrated elevated serum IL-6 and IL-17 levels in RA patients with depressive symptoms [74].…”
Section: Il-6 In Physical Diseases Associated With Depressionmentioning
confidence: 96%
“…In addition, most RA cases were among people living in rural areas and the loss of labour force caused by disability further worsens the economic situation of these patients, which brings about heavy burden to their families and causes long‐term negative impact on patients. Since systematic autoimmune inflammation caused by RA can increase the risk of depression (Kim, Chanyang, Oh, & Choi, 2019), RA shares similar pathological basis with depression in the aspect of neurological–endocrine–immunological regulatory axis (Li, Y.C., Chou, Chen, Lu, & Chang, 2019; Lopresti, Maker, Hood, & Drummond, 2014; Slavich & Irwin, 2014). Unfortunately, the comorbidity of depression will further exacerbate physical disability and healthcare burden.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is conflicting evidence about a potential role of IL-17 in depressive states. [29][30][31] The main limitations of this study are its retrospective nature and the relatively small number of observed patients. Moreover, a survivorship bias may emerge as a consequence of the minimum follow-up time of 6 months and could result in a slight underestimation of non-responders.…”
Section: Discussionmentioning
confidence: 97%